Pengaruh literasi keuangan dan etika bisnis islam terhadap kinerja usaha (studi pada komunitas pengusaha tangan di atas (tda) di samarinda) (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Laila Rahmasari Effect of Financial Literacy and Islamic Business Ethics on Business Performance (Study of the TDA Entrepreneur Community in Samarinda). Supervised by Isna Yuningsih and Musviyani. This study aims to determine: The effect of financial literacy on the business performance of the TDA community in Samarinda. The influence of Islamic business ethics on the business performance of the TDA community in Samarinda. This research is a survey research. The research population is the Samarinda TDA community which has a business duration of one to five years in business operations and is included in the TDA Samarinda community Data collection techniques used were questionnaires or questionnaire tools. The sampling method used in this study was Purposive sampling with 100 respondents. The data analysis technique of this study is Multiple Linear Regression. The results showed that: Financial literacy has a positive effect on the business performance of the Samarinda TDA community with a t-test significance value smaller than the specified level of significance; Islamic business ethics had a positive effect on the business performance of the TDA community in Samarinda with a significant value of the t-test smaller than the specified level of significance.